Design of topic priority based on industrial publish-subscribe system - Chen, Dejian; Li, Dong; Guo, Renchun (Frontiers in Energy Research, 2022)
As the size of the industrial systems increase, more and more topic messages need to be published and subscribed in industrial scenarios such as microgrid, manufacturing, etc. A priority scheduling algorithm based on the hotness of message topics is proposed to address the problem of efficient distribution of messages with different topics in microgrids. It is an algorithm that gives different priority permissions according to the number of topics, so that in the face of a large number of different topic messages, the data messages with higher number or urgency can be transmitted first, solving the problem of port blocking when the server distributes the messages. At the same time, in order to prevent low priority data from sending timeout or waiting for a long time, a time period is set up, a low priority transmission mechanism is set up within a specific time period to ensure that the system can send data to customers in a timely and accurate manner. The results show that the priority design in this paper can well solve the power scheduling problem of multi-target data transmission and ensure the transmission efficiency of messages in the microgrid system.